La correpetición en la enseñanza del violín y su incidencia en el desarrollo del oído armónico en los estudiantes de violín de quinto año de básica media y sexto de educación básica superior del colegio de artes Salvador Bustamante Celi de la ciudad de loja en el periodo 2018 – 2019. - Roa Marín, Michelle Elizabeth (2020)
The musical teaching institutions of our city and our country, primarily use Western tonal music, which is conceived in three dimensions: rhythm, melody and harmony. The violin, being a melodic instrument, has great disadvantages when it comes to teaching; among them, the little interest received by the development of the harmonic ear. The different methods used in the beneficiary institution are merely a compilation of technical and melodic studies, but those do not stimulate the harmonic element of music. Given this, pedagogical material, that actively involves teachers and students, has been developed. The main objective of the present investigation is “Contribute to the musical pedagogical development in the fifth year violin students of middle education and sixth year of Higher Basic Education of Salvador Bustamante Celi School of Arts, located in Loja city in the period 2018 - 2019”; and it pretends to be fulfilled through the following specific objectives: “To determine if the School of Arts can supply enough correpeting teachers”; “Define the repertoire program used by violin teachers in the institution strings area for students in fifth year of middle school and sixth year of senior school”; “Contribute to the development of the harmonic ear through a proposal with adaptations for strings group as support material for the interpretation of the repertoire program of the fifth year students of middle school and sixth year of high school in the subject of instrument - violin offered in the curriculum of baccalaureate in arts of the School of Arts Salvador Bustamante ”, and, “ Socialize the results and the proposal”. Thanks to the survey applied to the 16 violin teachers of the beneficiary Institution, it was perceived that there are not enough correpetitors and, therefore, the need for piano accompaniment during the student training process could not be met, causing this resource to be postponed to the final stage commonly called "The recital". On the other hand, the interview showed the alternatives that the authorities of the institution have implemented to solve this shortage, and also exposed the guidelines used to distribute the contents and the pedagogical repertoire of each year. Given this, the adaptation of the pedagogical repertoire is proposed, for its performance in chamber music (specifically, duets), which are easy to apply. Finally, with the observation 5 technique it was possible to discern which works are the most suitable for this research, taking into account the violin program and discarding those compositions that already had similar arrangements. This material benefited teachers and students of the study universe, although it also contributed students from other educational levels in an indirectly approach. Additionally, it is important to mention that the present investigation is consistent with the second line of research proposed by the music education career “Music as a learning enhancer in the educational process of the human being, program four“ Music as an educational practice, project four "Methods, techniques and strategies for musical teaching".